Nonalcoholic Steatohepatitis in Nondiabetic Obese Patients - Idilio Zamin; Angelo Alves de Mattos; Cláudio Galeano Zettler (Canadian Journal of Gastroenterology)
BACKGROUND: Nonalcoholic steatohepatitis (NASH) is a major disorder in patients with persistent changes in aminotransferase activity who test negative for viral markers and autoantibodies. Although NASH has been correlated with obesity, no study has been carried out exclusively with nondiabetic obese patients.